2008
DOI: 10.4049/jimmunol.181.11.7689
|View full text |Cite
|
Sign up to set email alerts
|

Retinoic Acids Are Potent Inhibitors of Spontaneous Human Eosinophil Apoptosis

Abstract: Retinoic acids (RAs), which are active metabolites of vitamin A, are known to enhance Th2-type immune responses in vitro, but the role of RAs in allergic inflammatory cells remains unclear. In this study, we demonstrated that purified peripheral blood eosinophils expressed nuclear receptors for RAs at the mRNA and protein levels. Eosinophils cultured with all-trans RA (ATRA) and 9-cis-RA showed dramatically induced cell survival and nuclear hypersegmentation, and the efficacy of RAs (10−6M) was similar to that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
38
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 47 publications
(42 citation statements)
references
References 59 publications
(35 reference statements)
0
38
0
1
Order By: Relevance
“…Interestingly, IL-7 and IL-15 are well known to regulate T cell homeostasis in the small intestine and it is tempting to speculate that both cytokine synergistically might contribute to eosinophils survival in the intestine, either directly or indirectly by stimulation of classical hematopoietins. Moreover, retinoic acid has recently been reported to inhibit eosinophil apoptosis (23), adding another facet to the complex array of factors abundantly present in the intestine and connected to eosinophil survival.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, IL-7 and IL-15 are well known to regulate T cell homeostasis in the small intestine and it is tempting to speculate that both cytokine synergistically might contribute to eosinophils survival in the intestine, either directly or indirectly by stimulation of classical hematopoietins. Moreover, retinoic acid has recently been reported to inhibit eosinophil apoptosis (23), adding another facet to the complex array of factors abundantly present in the intestine and connected to eosinophil survival.…”
Section: Discussionmentioning
confidence: 99%
“…Gelsolin is thought to play a role in degranulation (4) and adherence to target cells. The synaptic vesicle protein VAT-1 may play a role in antiapoptotic and prosurvival mechanisms, typical of several cytokines (11). The spot for ezrin was also increased, but this was not statistically significant.…”
mentioning
confidence: 91%
“…Eosinophils were isolated by sedimentation with 6% dextran followed by centrifugation on 1.088 Percoll (Pharmacia, Uppsala, Sweden) density gradients. The cells were further purified by negative selection using anti-CD16 immunomagnetic beads and a MACS system (Miltenyi Biotec, Bergisch Gladbach, Germany) as previously described [13,14]. Eosinophil purity of >98% was routinely obtained.…”
Section: Methodsmentioning
confidence: 99%
“…Among their isoforms, PPARα and PPARγ are targets for various long-chain fatty acids, including n-3 PUFAs [12]. In the case of eosinophils, PPARγ might be involved; we previously reported that both PPARγ and its heterodimer partner, retinoid X receptor (RXR), were constitutively expressed in human peripheral blood eosinophils [13,14]. In addition, in vitro experiments have revealed that both selective PPARα agonists and PPARγ agonists inhibit eosinophil survival and eotaxin-induced chemotaxis [14,15,16].…”
Section: Introductionmentioning
confidence: 99%